The "busy life" of unliganded estrogen receptors. Issue 2 (17th December 2015) - Stellato, Claudia; Porreca, Immacolata; Cuomo, Danila; Tarallo, Roberta; Nassa, Giovanni; Ambrosino, Concetta
Abstract : Understanding of the role of estrogen receptors (ERα and ERβ) in the pathophysiology of breast cancer (BC) has considerably increased in last decades. Despite sharing a similar structure, these two transcription factors often exert opposite roles in BC. In addition, it has been shown that their transcriptional activity is not strictly associated to ligand activation and that unliganded ERs are able to "have a life on their own." This appears to be mainly due to ligand‐independent mechanisms leading to ERs PTMs or to their recruitment to specific protein complexes, dependent on cellular context. Furthermore, a significant unliganded ER activity, probably independent by the activation of other pathways, has been recently reported to affect gene transcription, microRNA expression, and downstream proteome. In this review, we describe recent findings on nuclear and cytoplasmic unliganded ERα and ERβ activity. We focus on functional genomics, epigenomics, and interaction proteomics data, including PTM induced by ERs‐modulated miRNAs in the BC context. A better comprehension of the molecular events controlled by unliganded ERs activity in BC pathogenesis is crucial since it may impact the therapeutic approach to the initial or acquired resistance to endocrine therapies, frequently experienced in the treatment of BC.